2011
DOI: 10.3748/wjg.v17.i15.1989
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic duct guidewire placement for biliary cannulation in a single-session therapeutic ERCP

Abstract: Although DGT success rate proved not to be superior to SGT or pre-cut papillotomy, it is considered highly satisfactory in terms of safety in order to avoid the risk of a pre-cut when biliary therapy is necessary in difficult-to-cannulate cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…It stabilizes the papilla, closes the pancreatic duct and guides the second guidewire into the biliary axis by straightening the axis. 15,22,23 Other studies showed a success rate of 80-90% 13,14,16,20 at least equal to the pre-cut techniques. The DGW technique allows catheterization of the CBD in 45-90% of patients after failure of the standard technique.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It stabilizes the papilla, closes the pancreatic duct and guides the second guidewire into the biliary axis by straightening the axis. 15,22,23 Other studies showed a success rate of 80-90% 13,14,16,20 at least equal to the pre-cut techniques. The DGW technique allows catheterization of the CBD in 45-90% of patients after failure of the standard technique.…”
Section: Discussionmentioning
confidence: 93%
“…24,25 Some studies showed that insertion of a guidewire and/or contrast medium injection into the pancreatic duct significantly increased the risk of PEP, [12][13][14] whereas other studies showed no significant link. 24,25 Some studies showed that insertion of a guidewire and/or contrast medium injection into the pancreatic duct significantly increased the risk of PEP, [12][13][14] whereas other studies showed no significant link.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a small possibility of not inserting a pancreatic stent, which is per se associated with an increase in the PEP rate [28]. A study involving 146 patients in whom pancreatic stenting was attempted after PGW-assisted cannulation reported an unsuccessful rate of 14%; the rate of pancreatitis was 4.2% in the stent group versus 29% in the group in which it was not possible to insert a stent [29]. …”
Section: Discussionmentioning
confidence: 99%
“…However, another RCT showed a higher rate of PEP in patients undergoing DGT as opposed to SGT (17% vs. 8%) 27. On the other hand, a retrospective study did not show a significant difference in the rate of PEP between the two techniques (5.3% vs. 6.1%) 28. In an RCT, the incidence of PEP was lower in a 5-Fr pancreatic stent (PS) placement group than in a non-PS placement group after DGT (2.9% vs. 23%) 29.…”
Section: Specific Endoscopic Techniquesmentioning
confidence: 93%